Prevalence of Dermatological Problems in Beta-Thalasemic Patients at Al-Khidmat Hospital, Peshawar - Shahzad Rashid Awan, Muhammad Fahim, Saba Shaheen, Naveed Qamar, Jamshida Iqbal Khattak, Abdul Qayum Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Beta-thalassemia is the world's most prevalent single-gene disease with a reduction in the synthesis of hemoglobin b-chain. A lot of skins problems occur in thalassemia patients but, no study have been conducted in Pakistan to determine their prevalence. Objective: To determine the prevalence of dermatological problems in beta-thalasemic patients Methodology: This was cross sectional study carried out at the department of dermatology Al-Khidmat hospital Peshawar for a period of one year from August 2020 to August 2021. All the beta-thalassemia patients were examined for dermatological problems by a single expert dermatologist. All of the data was entered and analyzed by using the SPSS version 20 software. Results: Amongst 150 beta-thalasemic patients, 122 (81.33%) patients were observed with dermatological problems. The most frequent dermatological problem observed in our study was pruritus in 54 (36%) patients followed by xerosis in 34 (22.67%), urticaria in 30(20%), Pigmentary disorders in 33(22%) patient, freckles in 24(16%), tinea infections in 15(10%), pitriasis alba in 13 (8.67%) patients, scars in 13 (8.67%), hypersensitivity to deferoxamine pump in 12 (8%), herpes simplex in 12 (8%), Verruca vulgaris in 10 (6.67%), acne in 8 (5.33%) patients, miliaria in 8 (5.33%) while contact dermatitis was observed in 6(4%) of the patients. Conclusion: Our study concludes that dermatological problems are highly prevalent in beta-thalassemia patients with pruritus as the most common problem followed by xerosis. Keywords: Prevalence; Dermatological problems; Beta-thalasemia; Pruritus; Xerosis.